(SELADP]VXLMFV SURVFDDLVFLV VXJ NRDRSAKRNRDLAs - Mcafee Julie G; Shipley Kenneth G (Gotsis, 2013)
(SKFOFNLA XJV AQLRNRDJVJV AQLRNRDJVJ VF SRNLXLVOLMR SNALVLR VYNNRDJ SNJURZRUL]P SUR XJV AQLRNRDJVJV VYPFMXLOJVJ X]P VYNNFDROFP]P SNJURZRUL]P AQLRNRDJVJV MAXADUAZJ X]P FYUJOAX]P MAL YSRBRNJ FMKFVF]Ps
(SKFOFNLA XJV AQLRNRDJVJV AQLRNRDJVJ VF SRNLXLVOLMR SNALVLR VYNNRDJ SNJURZRUL]P SUR XJV AQLRNRDJVJV VYPFMXLOJVJ X]P VYNNFDROFP]P SNJURZRUL]P AQLRNRDJVJV MAXADUAZJ X]P FYUJOAX]P MAL YSRBRNJ FMKFVF]Ps